2000
DOI: 10.1093/oxfordjournals.jbchem.a022833
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Optimizing Protease/Peptide Inhibitor Interactions, a New Application for Spot Synthesis

Abstract: A new method is presented that uses parallel peptide array synthesis on cellulose membranes to characterize protease/peptide inhibitor interactions. A peptide comprising P5-P4' of the third domain of turkey ovomucoid inhibitor was investigated for both binding to and inhibition of porcine pancreatic elastase. Binding was studied directly on the cellulose membrane, while inhibition was measured by an assay in microtiter plates with punched out peptide spots. The importance of each residue for binding or inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…It can be concluded that a complete substitutional analysis is a valuable method for optimizing peptide inhibitors, as we previously showed in a similar approach for elastase inhibition (Hilpert et al, 2000). In that case, the directly measured elastase binding to cellulose-bound peptide spots correlated satisfactorily to inhibition measurements with solubilized peptides.…”
Section: Discussionsupporting
confidence: 65%
“…It can be concluded that a complete substitutional analysis is a valuable method for optimizing peptide inhibitors, as we previously showed in a similar approach for elastase inhibition (Hilpert et al, 2000). In that case, the directly measured elastase binding to cellulose-bound peptide spots correlated satisfactorily to inhibition measurements with solubilized peptides.…”
Section: Discussionsupporting
confidence: 65%
“…Immobilized arrays of peptides have been used for several applications including the identification of important residues in proteinprotein recognition, 1,2 the study of peptide-DNA interactions, 3 the enzymatic modification of peptides, 4,5 and the characterization of peptide motifs important to cell adhesion. 6,7 Many of these advances have been accomplished using multiplexed peptide arrays fabricated by SPOT synthesis.…”
mentioning
confidence: 99%
“…Also, to maintain the important disulfide bridges, the sequence of the inhibitory peptide PMT-LEYR was modified in position 2 to PCTLEYR. Furthermore, to avoid problems with an adjacent positive charge, and since a substitution for methionine is possible without decreasing inhibition (2,8), the Arg-7 was changed to methionine, a conserved position in most squash inhibitors. This inhibitor with the N-terminal sequence now reading PCTLEYM (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we described a method for characterizing and optimizing peptide inhibitor/ protease interactions using cellulose-bound peptides (2). We demonstrated an optimization process for a 9-mer peptide originating from the third domain of the turkey ovomucoid inhibitor, OMTKY3.…”
mentioning
confidence: 99%